Transforming Microfinance Institutions in the Arab World : Opportunities, Challenges and Alignment of Interest - International Finance Corporation (International Finance Corporation, Washington, DC, 2018)
Transformations in the microfinance industry have been widespread practice globally since the late 1990s. Currently, transformed MFIs transact the bulk of all microfinance operations, measured by number of clients as well as portfolio size. However, the few transformations that have taken place in the Arab World have mostly involved transforming international microcredit programs into registered institutions, with many of them remaining unregulated. The reasons for this are mostly related to the broader enabling environment and to legal frameworks and regulations that include an increase in taxes owed under the new legal status. In addition, concerns of mission drift, long central to discussions of transformation, have led to skepticism of the process altogether. Lastly, MFI employees may have concerns about the transformation process, ranging from their personal beliefs to uncertainty about their future under a new for-profit company. In recent years, however, regulations in some Arab countries have changed, and other barriers to transformation, such as concerns about mission drift and doubts among staff, have been handled with greater delicacy and success. Accordingly, the time has come to take a closer look at what this process might entail. This paper presents the Arab context, and discusses the benefits, costs, challenges, and opportunities associated with transforming a not-for-profit into a for-profit entity – not necessarily a bank. While what has worked elsewhere may not necessarily be applicable in the Arab World, the body of evidence is quite clear that institutional growth is sustained by a variety of funding channels, and that the opportunity to grow and better serve the underserved has encouraged many MFIs in the Arab World to reconsider transformation. This study also presents the results of a survey conducted jointly by IFC and Sanabel to better understand where MFIs in the Arab World currently stand in the transformation process. The survey was sent by email to a select group of MFIs that are either the leading MFIs in their countries or have already expressed interest in transformation. It was composed of two sections. The first collected background information, particularly about their current legal structure and plans to transform. The second was addressed to MFIs that have already transformed or are considering transformation, to understand how they view the benefits and challenges. As a part of this undertaking, the survey also asked questions about the MFIs’ interest in allowing staff to participate in the transformed entity’s equity by setting up an employee stock option plan (ESOP). This is a form of staff compensation in which select staff are awarded shares in the share-capital company that employs them. A few MFIs in other regions have implemented ESOPs during transformation to address staff concerns, reward demanding work, and align individuals’ goals with those of the institution. The survey sought to measure interest in ESOPs among respondents, as well as ask how they view the benefits, challenges, and appropriate terms of ESOPs. For MFIs wishing to explore this concept more deeply, Annex I of this paper addresses ways to implement ESOPs, and presents examples of MFIs that have elected to offer them.